Evaluating St. Augustinegrass (Stenotaphrum Secundatum (Walt.) Kuntze) Cultivars to Reduced Light Environments - B. McCarty, Lambert; J. Gambrell, Nathaniel (Journal of Agronomy Research, 2023)
St. Augustinegrass (Stenotaphrum secundatum (Walt.) Kuntze) generally has poor cold tolerance yet good to excellent shade tolerance. As mostly hot summers follow cold winters in USDA Hardiness Zone 7, severely damaging tall fescue (Lolium arundinaceum (Schreb.) Darbysh.) and centipedegrass (Eremochloa ophiuroides (Munro) Hack.), a St. Augustinegrass cultivar cold tolerant enough to be grown for shady lawns would greatly benefit home owners, recreational sites, and sod growers in the “transition zone.” Eight St. Augustinegrass samples were selected, including industry standards ‘Raleigh’ and ‘Palmetto’, plus ‘Palisades’ zoysiagrass (Zoysia japonica Steud.) for further testing from an established germplasm collection of material collected from lawns grown in USDA Hardiness Zone 7. Overall, based on 8-week greenhouse studies, the experimental lines had similar shade tolerance compared to commercial standards ‘Raleigh’ ‘Palmetto’ and ‘Palisades’ zoysiagrass. Field studies may be warranted to validate greenhouse studies to help further evaluate shade tolerance of experimental and commercial lines. Information generated supports the use of certain St. Augustinegrass selection in a wider environmental conditions such as reduced light environments (RLE).
Keywords: Chlorophyll; Photosynthetic Photon Flux (PPF); Shade; Transition Zone; Turfgrass; Zoysiagrass.